Empathy research framework in design thinking process through understanding the supra-functionality needs for home sofa furniture design in Malaysia - Haddadian, Mohammadali (2023)
The global market value of furniture was estimated to be worth 509.8 billion U.S. dollars in 2020 and 127.2 billion U.S. dollars in Home Furniture & Bedding. The Malaysian furniture industry focused on contributing RM19 billion in trades by 2025. Furniture items have come to a level of functional development. In order to attract the attention of the end-user, the designer has to offer added value in the field of pleasure, referred to as 'Supra-Functional needs', defined as attributes that satisfy users beyond their practical and functional needs. Users have long-lasting intimate sensory interactions with their sofa, making it a good case for studying supra-functional needs. The main problems in this respect are a lack of pleasurable home sofa fit the different user's purchasing power and difficulty expressing and understanding supra-functional needs. Therefore, there is a need for an alternative empathy research method for understanding users' supra-functional needs. The general research question is "How can an empathy research method uncover the supra-functional needs of users in a home sofa furniture?" and the main research objective is "to determine the criteria for an alternative empathy research method in the Design Thinking process". This study used mixed methods research, that combined both qualitative and quantitative methods because empathy is the exploration and collection of qualitative data supported and complemented by the quantitative research method. Face-to-face interviews were conducted to collect qualitative data from furniture stakeholders. The coding approach was used to code and analyse the qualitative data by ATLAS.ti software. Descriptive statistics, two-way ANOVA and Spearman correlation in SPSS software were used to analyse the quantitative data collected from home sofa end-users through Google Form Likert- scale questionnaire. Significant findings are: The main visual attributes of a sofa that Malaysian families positively perceive in the order of priority are shape, colour, material and texture. The features of the end-user that are relevant to understanding the end-users supra-functional needs are the user's gender, household income education and race. Sixteen criteria have emerged for the alternative empathy research method. These criteria are categorised into four main groups: virtual contact with users, using nonverbal techniques, attention to main supra-functional factors in sofa context, and considering market segmentation. Findings show an alternative empathy research method that uses online and visual approaches and considers end-user's preferences and expectations. Furthermore, segments of the sofa market can uncover the end-user supra-functional needs. The researcher suggests that end-user's visual and online data be collected by categorising style and supra-functional ranking tasks. To summarise the research findings, the researcher has created a framework for understanding end-user supra-functional needs in the home sofa in the Malaysian furniture market. The researcher conducted a validation process with furniture designers to ensure that this framework is valid. Overall validation results were based on three main categories, which were application, ease of implementation and benefit. The validation result shows that the framework is applicable with a high mean of benefit. However, it is a medium mean for application and a low mean for ease of implementation.